2005
DOI: 10.1002/jnr.20406
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of sciatic nerve in a Charcot‐Marie‐Tooth disease type 1a mouse model

Abstract: Expression profiling was performed on sciatic nerve of normal mice and of transgenic mice overexpressing the peripheral myelin protein 22 kDa (PMP22). These mice represent a model for the hereditary peripheral neuropathy Charcot-Marie Tooth type 1A. Comparison of the profiles reveals that the proteasomal degradation pathway and various signaling mechanisms are up-regulated in the diseased nerve. The down-regulated processes represent cell shape and adhesion as well as cellular activity and metabolism. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In contrast, transcripts related to cell proliferation were upregulated [96]. Both studies reported the downregulation of mRNA for ciliary neurotrophic factor (CNTF) [96,97]. Both studies reported the downregulation of mRNA for ciliary neurotrophic factor (CNTF) [96,97].…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…In contrast, transcripts related to cell proliferation were upregulated [96]. Both studies reported the downregulation of mRNA for ciliary neurotrophic factor (CNTF) [96,97]. Both studies reported the downregulation of mRNA for ciliary neurotrophic factor (CNTF) [96,97].…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…Our data provide proof of principle that mimicking the S100A4 activity by H3 administration protects axons from secondary injury in the context of severe demyelination in a P 0 model. Further studies should be carried out to clarify whether this effect is limited to the particular context of the P 0 deficiency, or it can be extended to other demyelinating or axonal forms of CMT (53,54). At least two mechanisms may underlie the effects of H3 in the PNS.…”
Section: S 1 0 0 M I M E T I C a F F E C T S R E G E N E R A T I O N mentioning
confidence: 99%
“…Recently, two different studies using cDNA micro-array of 30-day-old PMP22-overexpressing rats [56] or serial analysis of gene expression of adult PMP22-overexpressing mice [53] have shown similar up-regulation of genes related to cell proliferation and down-regulation of genes involved in cell cycle regulation, lipid and glucose metabolism, extracellular matrix formation and myelination. In addition, a very elegant study by GiamboniniBrugnoli et al [55] has attempted to delineate common as well as divergent mechanisms in animal models of hereditary neuropathies based on different PMP22 mutations.…”
Section: Animal Models Of Inherited Neuropathiesmentioning
confidence: 99%
“…Recently, gene expression profiles have been obtained from nerve samples of Charcot-Marie-Tooth disease (CMT) type 1A animal models [53,55,56] . In these studies, the genes identified may be responsible for causing the functional deficits and suggest pathways/processes that require further investigation as possible targets for therapeutic interventions.…”
Section: Gene Profilingmentioning
confidence: 99%
See 1 more Smart Citation